Microwave Assisted Synthesis and Characterization of Azomethines of Aryl Thiazole - Niraimathi, V.; Jerad Suresh, A.; Kokila, R. (Asian Journal of Chemistry, 2011)
2-Chloro-N-(2-methylphenyl)acetamide compound (I) was prepared by treating o-toludine, chloroacetyl chloride in alkali medium. The compound (I) was further treated with thiourea in alcohol and irradiated in microwave oven for 20 min to get (N4-phenyl-1,3-thiazole-2,4-diamine) compound (II). Five different azomethines were prepared by treating compound (II) with five different aldehydes in alcohol under reflux. The synthesised compounds were characterized by IR, mass, 1H NMR spectroscopy.